2004
DOI: 10.1260/026361704323151006
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Kinetics of Defluoridation Using Low-Cost Adsorbents

Abstract: Column kinetics for fluoride ion removal could be described more adequately by the Lobenstein model than by conventionally used models. This model can be used in a linearized form. Use of this model minimizes the error resulting from use of conventional models, especially at lower or higher time periods of the breakthrough curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…5 The materials developed for this purpose include hydrated cement, 6 alumina containing bauxite, 7 activated carbon, 8 calcite, 9 fly ash, 10 red mud, 11 synthetic hydrous Fe(III) oxide, 12 Zr(IV) oxides, 13 lime and Al salts, 14,15 and La-impregnated silica gel. 16 Apart from these, adsorbents prepared from natural materials such as dry powder of holly oak, neem bark powder, lime stone, clay, concrete, jute, activated carbon, and leaf powder 17,18 have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…5 The materials developed for this purpose include hydrated cement, 6 alumina containing bauxite, 7 activated carbon, 8 calcite, 9 fly ash, 10 red mud, 11 synthetic hydrous Fe(III) oxide, 12 Zr(IV) oxides, 13 lime and Al salts, 14,15 and La-impregnated silica gel. 16 Apart from these, adsorbents prepared from natural materials such as dry powder of holly oak, neem bark powder, lime stone, clay, concrete, jute, activated carbon, and leaf powder 17,18 have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…At low concentrations, it has beneficial effects on teeth; however excessive exposure to fluoride causes adverse health effects [4]. An intake of more than 6 mg fluoride per day will result in fluorosis [5]. Higher level of fluoride in ground water is a world-wide problem.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the regression coefficient (R 2 ), the Langmuir model (R 2 = 0.9473) was found to be the better fit than the Freundlich (R 2 = 0.9284) and Temkin (R 2 = 0.9298) isotherm models. Similarly, various studies reported either Freundlich isotherm model [35,39] or Langmuir isotherm model [37,49] as the better fit to explain the biosorption behaviour of various adsorbents involved in the removal of fluoride ions. [10].…”
Section: Resultsmentioning
confidence: 99%